Comparing school mathematics curriculum between Switzerland and Indonesia - Istihapsari, Vita; Junaedi, Iwan; Mulyono, Mulyono (Bulletin of Applied Mathematics and Mathematics Education, 2021)
Comparing a curriculum with the other more developed countries is essential for benchmarking the quality of education in the country. Switzerland deserves to be the object of comparison with the world's second-ranked Human Development Index. This article aims to compare the current curriculum in Indonesia, namely the 2013 curriculum, with the current curriculum in Switzerland, especially on school mathematics. The focus of the comparison lies in (1) school mathematics curriculum and (2) school mathematics content. This research is a qualitative research type of library research. We conducted a literature study, paid attention to the relevance of the literature, and analyzed it using data presentation, data reduction, and concluding. The results showed that with the education system in Switzerland, which emphasizes vocational education, the school mathematics curriculum places more emphasis on problem-solving. The contents are numbers, algebra, geometry, probability and statistics, changes and relationships, and problem-solving. Meanwhile, in Indonesia, the school mathematics curriculum is designed for every level of education with problem-based learning, project-based learning, and discovery learning models. School mathematics content includes numbers, algebra, geometry, relations and functions, statistics, and probability.